2021
DOI: 10.1021/acsestwater.1c00193
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the Reactivity of Superoxide Radicals with a Sulfonamide Antibiotic, Sulfacetamide: An Experimental and Theoretical Study

Abstract: Superoxide radical (O2 •–) is a ubiquitous reactive oxygen species in sunlit natural waters. Here, we selected sulfacetamide (SCT) as a representative sulfonamide antibiotic to investigate its reactivity with O2 •–, as this reaction was reported to be fast with the rate constant k of 7.0 × 107 M–1 s–1. The degradation kinetics of SCT were first studied in the classic McDowell systems (i.e., ultraviolet, acetone, and alcohols) for optimal O2 •– productivity. Comparison of the apparent first-order degradation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The in situ long-path spectroscopic approach used to generate O 2 •– in aqueous solutions was described in our previous study in great detail. , Briefly, O 2 •– was generated by 30 s UV irradiation of a buffered solution containing 5 μM DTPA, 5 mM H 2 O 2 , and 5 mM FA at pH 8. Because small quantities of metal ions ( e.g., Fe 3+ , Cu 2+ , etc. )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ long-path spectroscopic approach used to generate O 2 •– in aqueous solutions was described in our previous study in great detail. , Briefly, O 2 •– was generated by 30 s UV irradiation of a buffered solution containing 5 μM DTPA, 5 mM H 2 O 2 , and 5 mM FA at pH 8. Because small quantities of metal ions ( e.g., Fe 3+ , Cu 2+ , etc. )…”
Section: Methodsmentioning
confidence: 99%
“…The identification of O 2 •− generated in the aqueous solutions has been confirmed by both comparing the UV spectra under pulse radiolysis and chromogenic reactions with nitro-blue tetrazolium (NBT), which has been discussed in great detail in our previous studies. 31,32 Generation of O 2…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…reported the k value of sulfacetamide (SCT), a representative antibiotic, and O 2 •– to be fast with the rate constant k of 7.0 × 10 7 M –1 s –1 . We reevaluated this k value in a recent study, and all experimental and theoretical evidence indicated that the measured k value is 6 orders of magnitude smaller than the reported one . In addition, two studies reported that O 2 •– is linked to fast degradation of PFOA, , which is contradictory to the study by Javed et al .…”
mentioning
confidence: 71%
“…22 We reevaluated this k value in a recent study, and all experimental and theoretical evidence indicated that the measured k value is 6 orders of magnitude smaller than the reported one. 23 In addition, two studies reported that O 2…”
mentioning
confidence: 99%
“…The various radicals and anions formed by the two pathways are shown in Figure 3b,c. The nucleophilic nature of superoxide radicals would inhibit a radical/nucleophilic attack on the benzene ring (Bai et al, 2021; Luo et al, 2021). Moreover, the benzene ring has a high electron density due to the hydroxide group that would enhance repulsion to the negatively charged superoxide radical anion, thereby slowing the reaction (Min et al, 2022).…”
Section: Reaction Of Individual Plasma Species With Polyphenolmentioning
confidence: 99%